Islamic Financial Planning: How Far Has Been Researched? - Hasna Luthfi; Mimma Maripatul Uula (Fara'id and Wealth Management, 2022)
This study aims to see the development of research "Islamic Financial Planning” around the world and research plans that can be carried out based on journals published on that theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Islamic Financial Planning” which comes from the Scopus database with a total of 114 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the research development blibliometric map "Islamic Financial Planning" in this world. The results of the study found that in the author mapping bibliometrics the author published the most research with the theme "Islamic Financial Planning” is Kamaruddin, M.I.H; Shahimi, S; Shahriar, K; Andayani, S; Bijma, H.H; and Aggarwal A. Furthermore, based on bibliometric keyword mapping, there are 5 clusters that can be research lines with topics related to principles and practice, family planning, impact of Covid-19 on financial sustainability, Islamic banking, and Entrepreneurship, Personal Health, and for the most used words are performance, family planning, bank, Islamic banking, and zakat.